2021
DOI: 10.3389/fcimb.2020.581535
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stem Cells Ameliorating Pseudomonas aeruginosa–induced Acute Lung Infection via Inhibition of NLRC4 Inflammasome

Abstract: BackgroundPseudomonas aeruginosa (PA) is one of the most common Gram-negative bacteria causing hospital-acquired pulmonary infection, with high drug resistance and mortality. Therefore, it is urgent to introduce new non-antibiotic treatment strategies. Mesenchymal stem cells (MSCs), as important members of the stem cell family, were demonstrated to alleviate pathological damage in acute lung injury. However, the potential mechanism how MSC alleviate acute lung infection caused by PA remains unclear.ObjectiveTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…This question is worthy of our in-depth study. Another most relevant finding is that Aj-NLRC4 is involved in phagocytosis ( Fig 10 ), while other (vertebrate) NLRC4 proteins are active in inflammasome activation and could even act antiphagocytically as part of inflammation [ 92 ]. We speculate that this completely different method of recruitment and the pathway by which pathogen invasion is resisted could occur because AjNLRC4 lacks the traditional LRR and CARD domains, making it unable to perform the corresponding functions of traditional NLRs.…”
Section: Discussionmentioning
confidence: 99%
“…This question is worthy of our in-depth study. Another most relevant finding is that Aj-NLRC4 is involved in phagocytosis ( Fig 10 ), while other (vertebrate) NLRC4 proteins are active in inflammasome activation and could even act antiphagocytically as part of inflammation [ 92 ]. We speculate that this completely different method of recruitment and the pathway by which pathogen invasion is resisted could occur because AjNLRC4 lacks the traditional LRR and CARD domains, making it unable to perform the corresponding functions of traditional NLRs.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that anthrax lethal toxin could induce NLRP1-dependent pyroptosis in mouse macrophages, which promoted lung inflammation and resultant exacerbation of ALI (149). Recently, Li et al found that the activation of NLRC4 inflammasome in macrophages triggered by pseudomonas aeruginosa infection led to pulmonary inflammatory damage, while Adipose-Derived Mesenchymal Stem Cells improved lung tissue damage in mice through reducing the NLRC4 inflammasome activation in macrophages (150). Wang et al found that HMGB1 could participate in LPS−induced of ALI by activating the AIM2 inflammasome in macrophages (151).…”
Section: Ali/ardsmentioning
confidence: 99%
“…The indirect antimicrobial effects of MSCs, partly mediated via Toll-like receptor (TLR) signaling [110], proved to (I) modulate proinflammatory cytokine and chemokine induction; (II) to release immunosuppressive factors that inhibit excessive proliferation and infiltration of inflammatory T cells and Natural Killer (NK) cells; and (III) to increase phagocytic activity of monocytes and neutrophils [111]. In addition to the inhibition of the NLRP3 inflammasome [112] by BM-MSCs [113], the ASCs [113] also reduced the activation of NLRC4 inflammasome [114,115], thereby increasing the phagocytic ability of macrophages induced by P. aeruginosa infection [116]. Treatment with MSCs diminished the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kb) in lung injury induced by sepsis [117].…”
Section: Mscs As Source Of Antibiotic-free Nanomaterialsmentioning
confidence: 99%